G- Contant of Generalied Veissman Grey Manifold - Abd, Abdulhadi (Indonesian Journal Publisher, 2025)
We shall examine the geometrical conharmonic tensor in this essay. The primary aim of this work is to examine certain geometric characteristics of the Veissman Grey manifold characteried by flat circular curvature. The flatness quality of the circular tandem is employed to establish essential conditions for the Veissman Grey manifold, as well as for locally conformal, Kohler, and manifolds, and to identify new relationships among them. Additionally, these manifolds possess classical characteristics that enable them to regain the Hermitical manifold's Riemannian structure. We also investigated the sectional curvature, which furnished us with a wealth of information regarding Riemannian geometry, a field that is essential to differential geometry. In order to keep these harmonic functions consistent, circular transformations played a significant role in Rumanian structural alterations.